A Governança e a concretização de políticas públicas na tutela dos vulneráveis: marco regulatório das licitações no âmbito da lei 14.133/21 - ALVES, Beatriz Dixon Moreira (2023)
ABSTRACT: The process of contracting goods and services by the government is an activity that is present in virtually all social areas, reflecting the scope of administrative functions that the Constitution and Brazilian laws attribute to the State. Consequently, the volume of public purchases in Brazil is significant in relation to the country's Gross Domestic Product (GDP). This proportion reflects the essential role the public sector plays in economic and social development, and how government procurement policies can have a substantial impact on sustainable national development. Law 14,133, enacted on April 1, 2021, has the primary objective of ensuring that public procurement achieves a "more advantageous result." By establishing sustainable national development as the purpose of the norm, it signals the importance of balanced and conscious growth, which aims to ensure the promotion of equal opportunities for all citizens. With this change, bidding ceases to be merely a secondary activity and becomes recognized as an essential function of the State to achieve the ends established by the Constitution. The present work aims to demonstrate how Law 14.133, of April 1, 2021, gives rise to the regulation of a public policy that protects the vulnerable. In the first chapter, good governance is approached as a major premise, preparatory to the fertile field for the teleological development of the protection of the vulnerable and the verification of the Federal Court of Accounts in relation to the current level of governance exercised by its jurisdictions. In the second chapter, it analyzes the normative content of Law 14.133, of April 1, 2021 and the specific precepts aimed at regulating public policy in the protection of the vulnerable. In the third chapter, the position of the Judiciary is verified in the tutelary implementation of the vulnerable that flow from the new bidding law and some regulations that, through public contracting, promote humanitarian protective policies. For the construction of the work, the hypothetical deductive method was adopted, with the purpose of confirming, in the end, the premise that the bidding is an instrument of public policies to protect the vulnerable. Indirect documentary research was used, with the analysis of legislation, doctrine and jurisprudence.